DNA Methylation Can Mediate Local Adaptation and Response to Climate Change in the Clonal Plant Fragaria vesca: Evidence From a European-Scale Reciprocal Transplant Experiment - Sammarco, Iris; Münzbergová, Zuzana; Latzel, Vít (Frontiers in Plant Science, 2022)
The ongoing climate crisis represents a growing threat for plants and other organisms. However, how and if plants will be able to adapt to future environmental conditions is still debated. One of the most powerful mechanisms allowing plants to tackle the changing climate is phenotypic plasticity, which can be regulated by epigenetic mechanisms. Environmentally induced epigenetic variation mediating phenotypic plasticity might become heritable across (a)sexual generations, thus potentially enabling rapid adaptation to climate change. Here, we assessed whether epigenetic mechanisms, DNA methylation in particular, enable for local adaptation and response to increased and/or decreased temperature of natural populations of a clonal plant, Fragaria vesca (wild strawberry). We collected ramets from three populations along a temperature gradient in each of three countries covering the southern (Italy), central (Czechia) and northern (Norway) edges of the native European range of F. vesca. After clonal propagation and alteration of DNA methylation status of half of the plants via 5-azacytidine, we reciprocally transplanted clones to their home locality and to the other two climatically distinct localities within the country of their origin. At the end of the growing season, we recorded survival and aboveground biomass as fitness estimates. We found no evidence for local adaptation, besides maladaptation of plants of the warmest populations. Plants treated with 5-azacytidine showed either better or worse performance in their local conditions than untreated plants. Application of 5-azacytidine also affected plant response to changed climatic conditions when transplanted to the colder or warmer locality than was their origin, the response was however country-specific. We conclude that the increasing temperature will probably be the limiting factor determining F. vesca survival and distribution. Epigenetic variation may contribute to local adaptation and response to climatic change in natural ecosystems, however its role may depend on the specific environmental conditions. Since adaptation mediated by epigenetic variation may occur faster than via natural selection on genetic variants, epigenetic adaptation might to some degree help plants in keeping up with the ongoing environmental crisis.